Prevalensi infeksi cacing usus yang ditularkan melalui tanah pada petani di Kelurahan Ranowangko Kecamatan Tondano Timur Kabupaten Minahasa - Wijaya, Raditya Putri; Tuda, Josef S. B.; Sorisi, Angle M. H. (UNIVERSITAS SAM RATULANGI, 2018)
Background: Helminthiasis was categorized as a neglected disease for its commonly found without significant clinical manifestation. According to World Health Organization (WHO) approximately there are 1,5 billion people in the world infected with Soil Transmitted Helminths (STH). This infection have been associated with health and productivity insults. Aims: This study was aimed to investigate prevalence of STH infection in farmers at Ranowangko, east side of Tondano. Method: This study is a cross sectional descriptive study. Result: Fifty four stool specimens were collected on November 2018 and were examined microscopically at Parasitology Laboratory, Sam Ratulangi University Manado. There were no positive results. Conclusion: Based on this study, all farmers in Ranowangko Tondano were not infected with STH.